Development and validation of a new triplex real-time quantitative reverse Transcriptase-PCR assay for the clinical detection of SARS-CoV-2. (August 2021) - Gadkar, Vijay J.; Goldfarb, David M.; Young, Virginia; Watson, Nicole; Al-Rawahi, Ghada N.; Srigley, Jocelyn A.; Tilley, Peter
Abstract: To increase the repertoire of PCR based laboratory developed tests (LDTs) for the detection of SARS-CoV-2, we describe a new multiplex assay (SORP), targeting the SARS-CoV-2's, S pike and O RF8 genes. The widely used human RNaseP internal control was modified to specifically co-amplify the RNaseP mRNA. The SORP triplex assay was tested on a cohort (n = 372; POS = 144/NEG = 228) of nasopharyngeal flocked swab (NPFS) specimens, previously tested for the presence of SARS-CoV-2 using a PCR assay targeting E and RdRp genes. The overall sensitivity and specificity of the SORP assay was: 99.31% (95% CI: 96.22–99.98%), 100.0% (95% CI: 98.4–100%) respectively. The SORP assay could also detect a panel of variants of concern (VOC) from the B1.1.7 (UK) and B1.351 (SA) lineage. In summary, access to a repertoire of new SARS-CoV-2 LDT's would assist diagnostic laboratories in developing strategies to overcome some of the testing issues encountered during high-throughput SARS-CoV-2 testing. Highlights: Multiplex real-time PCR assay targeting the SARS-CoV-2's Spike and ORF8 gene was developed. Novel human RNaseP reverse transcription internal control incorporated in the assay. Limit of detection of the S and ORF8 gene targets: 222.33 c/mL and 206.69 c/mL respectively. New assay detected SARS-CoV-2 variants of concerns belonging to the B.1.1.7 and B1.135 lineage.